Metabolic syndrome and parental history of cardiovascular disease in young adults in urban Ghana - Yeboah, k.; Dodam, k.k.; Affrim, P.K.; Adu-Gyamfi, L.; Bado, A.R.; Owusu Mensah, R.N.A.; Adjei, A.B.; Gyan, B. (BMC Public Health, 2017)
Background: Metabolic syndrome (MetS) in young adults poses significant cardiovascular diseases (CVD) risk for later years. Parental history of CVDs is known to affect the prevalence of CVD risk in adulthood. In sub-Saharan Africa, the burden of MetS in young adults and its relationship with parental CVDs is largely unknown. We studied the gender-specific prevalence of MetS and its association with parental history of diabetes, hypertension and CVDs in young adults resident in urban Ghana. Methods: In a cross-sectional design, 364 young adults aged 20-30 years were randomly recruited from students of University of Ghana. A structured questionnaire was used to collect data on demography, lifestyle, medical and parental medical history. Anthropometric indices and blood pressures were measured. Fasting blood samples were collected to measure plasma levels of glucose, lipid profile, urea and creatinine. MetS was defined according to the Joint Scientific Statement criteria. Results: The prevalence of MetS was 12.4%, higher in females than male participants (18.4% vs 5.7, p = 0.019). Female participants had higher levels of all the components of MetS than the male participants. Compared to participants with no history of parental CVDs, participants with parental CVDs had a higher proportion of abdominal obesity. A positive history of parental CVDs was associated with increase in odds of MetS [OR (95% CI): 1.23 (1.12-3.04), p = 0.037]. Conclusion: In our study population, there is relatively high prevalence of MetS; higher in females compared to male participants. Parental history of CVDs was associated with MetS. © 2017 The Author(s).
Keywords: lipid; abdominal obesity; adult; anthropometry; blood; cardiovascular disease; cross-sectional study; female; Ghana; glucose blood level; human; lifestyle; male; metabolic syndrome X; parent; prevalence; questionnaire; risk factor; sex ratio; young adult; Adult; Anthropometry; Blood Glucose; Cardiovascular Diseases; Cross-Sectional Studies; Female; Ghana; Humans; Life Style; Lipids; Male; Metabolic Syndrome; Obesity, Abdominal; Parents; Prevalence; Risk Factors; Sex Distribution; Surveys and Qu